2009
DOI: 10.1111/j.1365-294x.2008.04062.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryobanking of viable biomaterials: implementation of new strategies for conservation purposes

Abstract: Cryobanking, the freezing of biological specimens to maintain their integrity for a variety of anticipated and unanticipated uses, offers unique opportunities to advance the basic knowledge of biological systems and their evolution. Notably, cryobanking provides a crucial opportunity to support conservation efforts for endangered species. Historically, cryobanking has been developed mostly in response to human economic and medical needs -these needs must now be extended to biodiversity conservation. Reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 11 publications
0
44
0
1
Order By: Relevance
“…Not only are adult stem cells known to be proliferative over long time periods while keeping their ability for contact inhibition (Pittenger et al 1999, Poulsom et al 2002, but exocrine pancreatic tissue is a very efficient source for multi-and pluripotent adult stem cells in various species (Kruse et al 2006, Lermen et al 2009). In fact, the propensity of exocrine pancreatic tissue to yield high amounts of stem-or progenitor cells has been utilized to establish the CryoBrehm cell bank for viable cells of a large variety of endangered vertebrates (Lermen et al 2009, Ciba et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are adult stem cells known to be proliferative over long time periods while keeping their ability for contact inhibition (Pittenger et al 1999, Poulsom et al 2002, but exocrine pancreatic tissue is a very efficient source for multi-and pluripotent adult stem cells in various species (Kruse et al 2006, Lermen et al 2009). In fact, the propensity of exocrine pancreatic tissue to yield high amounts of stem-or progenitor cells has been utilized to establish the CryoBrehm cell bank for viable cells of a large variety of endangered vertebrates (Lermen et al 2009, Ciba et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated previously by Kruse et al (2004Kruse et al ( , 2006 and others (Seaberg et al 2004, Seeberger et al 2006, Gorjup et al 2009, Rapoport et al 2009) that proliferative cell populations can be obtained from exocrine pancreatic tissue with extraordinarily high yields. The preparation method used by Kruse et al (2004) to isolate these cells has been subsequently expanded towards other species, such as Burchell's zebra Equus quagga burchellii, marine otter Lontra felina, and snow leopard Uncia uncia (cells of these 3 species were stored in the 'Alfred Brehm' German Cell Bank for Wild Animals, also called Cryo-Brehm) (Lermen et al 2009, Ciba et al 2010. From these studies, we concluded that exocrine glandular tissue might generally be a potent source to obtain long-term growable cell cultures, also from fishes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ability to culture and/or harvest oocytes and spermatozoa from the gonadal tissues of livestock and then incubate to maturity offers near-unlimited genetic material for improving reproductive efficiency and food security. For rare genotypes or species as well, the capacity to produce viable germplasm from gonadal cells would ensure the reproductive capacity of every genetically valuable individual (Lermen et al 2009; Comizzoli et al 2010), thereby contributing to the ultimate goal of achieving population sustainability. This is important for animals that have not yet produced sufficient numbers of descendants, including those that: (1) are living, but have failed to reproduce naturally (perhaps due to sexual incompatibility, a physical defect or lack of partners); (2) die unexpectedly; (3) are nearing reproductive senescence; or (4) have been long dead, but their rescued genes have value when reinfused into the contemporary population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are common alignments; for example, the recognition that banks of frozen biomaterials are invaluable for preserving and enhancing reproductive potential and perpetuating an individual’s genome. All three of these scientific communities have long advocated the need to preserve biomaterials at cold temperatures (Wildt et al 1997; Mazur et al 2008; Lermen et al 2009; Baker 2012). For wildlife species, these ‘genome resource banks’ have been essential for managing selected rare species, as well as characterising the uniqueness of certain taxa (Wildt et al 1997; Lermen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation